Data Security System in Cloud by Using Fog Computing and Data Mining (International Journal of Engineering and Computer Science, 2016)
Cloud computing it can be defined as a group of computer and servers which connected together on network. Today, as many organization  and enterprises are beginning to adopt the IOT(internet of things),they all need for large amount of data to be accessed quickly, to be safe on cloud from attacker or insider then the security is also important mechanism to secure cloud data of  an  government organization or any IT-industry. Sometimes existing encryption data protection mechanisms failed in preventing data theft attacks from criminal attacker, especially from insider to the cloud provider. To provide security to cloud data from unauthorized access from malicious attacker we propose a different approach to securing data in cloud system by using decoy technology. We monitor user behavior or data access patterns in cloud system and identifying abnormal data access patterns. When any unauthorized data access patterns is suspected then decoy data is provided to the unauthorized user. This mechanism protects against the misuse of the user real data. If incase real user get trapped in this system then user can ask one time password for verification.